PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR PADA INDEKS SRI-KEHATI - Kusumaningtyas, Titah Kinanti; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of good corporate governance (include: managerial ownership, institutional ownership, the composition of the independent commissioner, and audit quality), to the firm value. Price Book Value is used as the proxy of the firm value. The samples are ten companies which are listed in the SRI-KEHATI index with a three-year study period. The method of analysis of this study is done by using multiple linear regressions. The result of this research indicates that managerial ownership, the composition of independent commissioner and the audit quality variable do not have any influence to the firm value. Whereas the institutional ownership variable has positive influence to the firm value.Keywords: Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Quality, and Firm Value